Cataract surgery barriers, cataract surgical coverage and outcome among rural population of Dhule district in Maharashtra - Patil, Sarika P.; Tambe, Muralidhar P.; Khan, Mukram G. G.; Patil, Prashant J.; Bawa, Mukesh S.; Pagar, Vikrant S. (International Journal Of Community Medicine And Public Health, 2020)
Background: In India the coverage and outcome of cataract management are through camps and hospital undertaking rural cataract surgical services. There are varied outcomes of cataract surgery in population based studies within our country while cataract surgical outcomes have inbuilt dependency on various factors. National program for control of blindness and visual impairment aims in improvement of vision of the cataract patients. Thus evaluating cataract outcome would help top strengthen the national program. Methods: The study was part of population based blindness survey carried out among 40 years and above rural population in Dhule district of Maharashtra during 2019. In the survey 2370 villagers, 40 years and above were surveyed for blindness prevalence by 30 Cluster sampling technique having 79 peoples from each cluster. Collection of baseline data with information of eye care services and ophthalmic examination was done. Results: Prevalence of cataract in 40 year and above population in study was 20.78%. In present study predominant barrier in cataract operation in 71.1% participants for not having consultation was belief it to be destiny or God’s will. 20.3% cataract patients with visual impairment had visual acuity of 6/60 and 18.4% had less than 3/60 visual acuity. Maximum participants had cataract operated in government hospital 61.7%. In the study cataract surgical coverage was 72.7% by eyes and 81.7% by person for visual acuity <3/60. Conclusions: Efforts to increase cataract surgical coverage would help to reduce the prevalence of visual impairment due to cataract.